Teachers’ Understanding and Practice of the Genre-Based Approach in Arabic Instruction at Indonesian Madrasahs - Jumhana, Nana; Mufrodi,; Fahmi, Teguh (Jurnal Pendidikan Islam, 2025)
Globally, the implementation of effective language teaching approaches remains a major challenge, particularly in contexts where curriculum reform and teacher capacity are uneven. This study aims to examine the problems in implementing the Genre-Based Approach (GBA) in Arabic language learning within Indonesian madrasahs, focusing on curriculum analysis and teacher practice. Using a qualitative design, the research was conducted across several madrasahs in Banten Province, where the researcher served as the primary data collection instrument through observation, interviews, and document analysis. The study analyzed Arabic curriculum documents issued under the Decree of the Minister of Religious Affairs (KMA) No. 183 of 2019 and the Director General’s Decree (Kepdirjen) No. 3211 of 2022, complemented by interviews with Arabic teachers. The findings reveal that most teachers have not applied the GBA due to limited training, inadequate socialization, and low comprehension of GBA principles. Additionally, the Arabic curriculum does not fully accommodate the text-based learning process central to GBA, partly due to its complex structure and low readability. These results highlight the need for targeted professional development and curriculum revision to strengthen Arabic language pedagogy and advance quality improvement in Islamic education.